Production of bioactive hepcidin by recombinant DNA tagging with an elastin-like recombinamer - da Costa, A. (2018)
With the lack of new chemical antibiotics and increasing pathogen resistance to those available, new alternatives are being explored. Antimicrobial peptides (AMPs) with a broad range of effects, including antibacterial, antifungal, and antiviral actions, have emerged as one of the options. They can be produced by recombinant DNA technology, but the chromatographic methods used for peptide purification are expensive and time consuming. Here, we describe the design, production, purification and assessment of the antibacterial activity of the human peptide hepcidin, using an elastin-like recombinamer as fusion partner. The recombinant protein Hep-A200 was produced in Escherichia coli and purified by a non-chromatographic procedure, exploiting the thermal properties of the A200 elastin-like recombinamer. Recombinant Hep-A200 was found to retain antibacterial activity against Gram-positive and Gram-negative species.